Laser surface treatment of 50CrMo4 steel - Chew, Han Xin (2018)
50CrMo4 is an alloy steel that is commonly used in engineering applications such as engine and machine technologies. This is due to their favorable characteristics of high hardness, high tensile strength, minimum yield strength and minimum elongation. In this project, experimental studies were conducted to analyze 50CrMo4 alloy steel sample in the influence of laser operating parameters. During laser hardening, study the effect of different purge gases. Study the change in surface properties before and after laser treatment. The alloy steel was tested with different laser operating parameters and purge gases. To analyze the data, Optical, Stereo and Scanning Electron images were collected. TalyScan, EDS and Hardness test were done on the alloy steel. After experiments on the steel with the effect of Power, Speed and Purge gases. The hardness value of the 50CrMo4 alloy steel was found to be in the range between 700HV and 800HV. The width and depth changes as the operating parameters and purge gas changes. The speed of laser is significance in affecting the width and depth of the laser treated lines. When the speed is too high, the change is not visible, thus, the hardness test cannot be done on the cross section area.